SINTESIS DAN KARAKTERISASI C-SINAMALKALIKS[4]RESORSINARENA (CSKR) MENGGUNAKAN MINYAK KAYU MANIS(CINNAMOMUM BURMANII) UNTUK ANALISIS ION LOGAM CR3+ - Susanti, Yuni Makdalena (journal of residu, 2019)
This study aims to determine the potential of C-SinamalKaliks [4] Resorsinarene (CSKR) as an adsorbent for the absorption of Cr3+ metal ions using optimum conditions parameters which are estimated to affect the Cr3+  absorption process. CSKR is synthesized by reacting cinnamaldehyde with resorcinol through an electrophilic substitution reaction. Cinnamaldehyde was obtained from isolation using cinnamon oil as much as 7.036 grams with a yield of 14.072% from 50 g cinnamon oil and CSKR produced as much as 5.6775 g brownish red. Cinnamaldehyde and CSKR were characterized using FTIR and UV-VIS. The results of the UV-VIS spectrum and FTIR data by the CSKR from isolated cinnamaldehyde showed the same results as pure cinnamaldehyde. The results of CSKR characterization using UV-VIS have absorption at a wavelength of 440 nm with an absorbance of     4.365 A which indicates that there is a double bond conjugated to cinnamaldehyde and CSKR. The results of CSKR characterization using FTIR showed a peak of 3806.68 cm-1 indicating the presence of an O-H group. Furthermore, there is absorption at wave number 1610.56 cm-1 which indicates the presence of C=C groups. At wave number 1448.90 cm-1 shows the aromatic ring. Furthermore, absorption at the fingerprint wave number 692.31 cm-1 - 836.05 cm-1 indicates the presence of (CH2). The CSKR melting point is 358⁰C. Analysis of Cr3+ ions in optimum conditions occurred at pH 4 with optimum contact time of 150 minutes and concentration of 100 ppm. The results of the analysis were validated which included precision testing and accuracy testing. The precision test value (% RSD) of Cr3+ metal ions produced was 1.52% and the test accuracy value (% recovery) was 122.917%. The test results explain that the method carried out fulfills good validation